Towards a Systemic Approach for Improving Working Conditions in Global Supply Chains: An Integrative Review and Research Agenda - Soundararajan, Vivek; Wilhelm, Miriam; Crane, Andrew; Agarwal, Pankhuri; Shetty, Harish (Academy of Management Annals, 2025)
In global supply chains, subpar working conditions are a critical issue affecting organizations, workers, civil society, and policymakers alike. Our objective is to evaluate the approaches to improve working conditions within global supply chains and their implications. Through a comprehensive review that integrates insights from various social science disciplines, we offer a fresh perspective on this challenge. We begin by identifying factors at multiple levels—supply chain, workplace, individual, and institutional—that contribute to poor working conditions, and explore how these factors, in some configuration, contribute to poor working conditions in different sample archetypes of global supply chains. We then present the factors driving lead organizations to improve working conditions in their global supply chains. Next, we dissect the transactional and relational approaches commonly implemented by lead organizations, assessing their mechanisms and effectiveness. Our review indicates that these approaches have limited success. As an alternative, we synthesize diverse insights to introduce a systemic approach grounded in three pivotal mechanisms: cooperation, recognition, and evolution. This approach aims to tackle the multifaceted factors affecting working conditions. To advance the systemic approach, we propose critical research questions that pave the way for future studies.